2018
DOI: 10.1038/s41598-018-28060-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of clinical and radiological findings for conservative treatment of idiopathic ulnar impaction syndrome

Abstract: Ulnar impaction syndrome (UIS) is a common source of ulnar-sided wrist pain, yet not all cases of radiographic ulnar impaction are symptomatic. We retrospectively analyze clinical or radiologic factors that affect prognoses of conservative treatment for idiopathic UIS. A total of 114 patients who had been diagnosed with UIS were treated with 6 weeks of short arm orthosis followed by formal physiotherapy for 6 weeks, with lifestyle modification to limit aggravating movements. The response to treatment, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…However, some other studies did not show any association between ulnar variance and sex (2,29,30). The association between ulnar variance and sex may in part explain that idiopathic ulnar impaction syndrome is more prevalent in women (31), whereas Kienböck's disease shows a male predominance (32,33). Although previous studies have suggested an association between negative ulnar variance and Kienböck's disease (2,3,26), the causality is uncertain (4).…”
Section: Discussionmentioning
confidence: 99%
“…However, some other studies did not show any association between ulnar variance and sex (2,29,30). The association between ulnar variance and sex may in part explain that idiopathic ulnar impaction syndrome is more prevalent in women (31), whereas Kienböck's disease shows a male predominance (32,33). Although previous studies have suggested an association between negative ulnar variance and Kienböck's disease (2,3,26), the causality is uncertain (4).…”
Section: Discussionmentioning
confidence: 99%
“…The conservative treatment regimen typically involves continuous splint fixation for 4 weeks and intermittent wear for 2 weeks, followed by 6 weeks of rehabilitation after the splint removal. 23 For patients experiencing significant ulnar-sided wrist pain, oral nonsteroidal anti-inflammatory drugs (NSAIDs) can be administered for symptomatic relief. In cases of severe ulnar-sided pain, especially when NSAIDs are not sufficiently effective, localized pain point blockade on the ulnar side of the wrist may be considered.…”
Section: Imaging Examinationmentioning
confidence: 99%
“…Conservative treatment for patients with UIS often spans a lengthy period, typically extending beyond 6 weeks, with a success rate usually <60%. 23,24 Identifying high-risk patients and reducing the time cost of awaiting surgery are crucial for an early return to daily life.…”
Section: Imaging Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In the absence of DRUJ instability, treatment approaches typically begin with conservative strategies employing immobilization as the primary treatment modality for 4 to 12 weeks. 1,[6][7][8][9][10][11] Although such initial nonoperative management is the conventional approach, 6,8 evidence has shown that up to 43% of patients with acute, stable TFCC tears managed by immobilization for a minimum of 4 weeks will eventually require surgery. 11 Furthermore, a recent study on the natural course of TFCC tears without DRUJ instability, in which patients were managed nonoperatively with 4 to 12 weeks of immobilization, found a 30% rate of complete recovery at 6 months and 50% at 1 year.…”
Section: Introductionmentioning
confidence: 99%